2015
DOI: 10.1186/s13071-015-1271-x
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of Galba truncatula as an intermediate host snail for Calicophoron daubneyi in Great Britain, with evidence of alternative snail species hosting Fasciola hepatica

Abstract: BackgroundFasciola hepatica is a highly prevalent parasite infecting livestock in Great Britain, while Calicophoron daubneyi is an emerging parasite within the GB livestock industry. Both F. hepatica and C. daubneyi require an intermediate host snail to complete their life-cycles and infect ruminants; however, there has been no confirmation of the intermediate host of C. daubneyi in GB, while there are questions regarding alternative host snails to Galba truncatula for F. hepatica. In this study, PCR was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 23 publications
(30 reference statements)
0
45
1
4
Order By: Relevance
“…Nevertheless, Abrous et al [15] showed that the role of this snail species as a transmitter was very limited (prevalence very low or nil) when G. truncatula was also present in the same habitat. Our findings in relation to F. hepatica do not appear to be consistent with those of Relf et al [17] and Jones et al [18], who detected parasite DNA in a high proportion of R. peregra snails in Ireland (66 out of 167) and the UK (13 out of 52). Nevertheless, the presence of live F. hepatica larvae in these snails was not definitely demonstrated (i.e.…”
Section: Discussioncontrasting
confidence: 92%
See 4 more Smart Citations
“…Nevertheless, Abrous et al [15] showed that the role of this snail species as a transmitter was very limited (prevalence very low or nil) when G. truncatula was also present in the same habitat. Our findings in relation to F. hepatica do not appear to be consistent with those of Relf et al [17] and Jones et al [18], who detected parasite DNA in a high proportion of R. peregra snails in Ireland (66 out of 167) and the UK (13 out of 52). Nevertheless, the presence of live F. hepatica larvae in these snails was not definitely demonstrated (i.e.…”
Section: Discussioncontrasting
confidence: 92%
“…According to the published data, similar or even lower prevalence rates are generally observed for infections caused by a great variety of trematode species, including C. daubneyi and F. hepatica , in lymnaeid populations in natural ecosystems [14, 16, 18, 30]. In a retrospective study carried out in Central France over a 12-year period, differences in the prevalence of C. daubneyi infection were observed in the definitive and intermediate hosts.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations